Среди нехоженых дорог одна - моя: сб орник туристских песен / сост. Л. П. Беленький - Беленький Л. П. (Профиздат, 1989)
Экземпляры: (20200323) / Инвентарный номер: 21510 / Цена: / Сис.шифр: Щ94я438 / Авт.знак: С 76 / ББК: Щ94я438